Common arterial trunk in the fetus: characteristics, associations, and outcome in a multicentre series of 23 cases. Issue 12 (14th November 2003) - Volpe, P; Paladini, D; Marasini, M; Buonadonna, A L; Russo, M G; Caruso, G; Marzullo, A; Vassallo, M; Martinelli, P; Gentile, M
Abstract : Objective: To assess the accuracy of prenatal diagnosis, the incidence of extracardiac and chromosomal anomalies, and the perinatal outcome in a population of fetuses with common arterial trunk (CAT). Design: Observational study of 23 fetuses from three referral centres with a confirmed diagnosis of CAT. All underwent fetal echocardiography, detailed anatomical scanning, and karyotyping. In 19 cases, FISH analysis was done to detect 22q11 microdeletion. The following variables were evaluated: gestational age at diagnosis, anatomical variants of the CAT, presence of extracardiac and chromosomal anomalies, pregnancy, and fetal–neonatal outcome. Necropsy reports and postnatal files were available for confirmation of the prenatal diagnosis in all cases. Results: The prenatal diagnosis proved correct in 23 of 24 cases, the last being pulmonary atresia with ventricular septal defect (PAVSD). A second cardiovascular anomaly was present in eight cases (34.8%); extracardiac anomalies were found in 10 (43.4%). FISH analysis showed 22q11 microdeletion in six of 19 cases (31.6%). Outcomes were as follows: eight terminations of pregnancy (34.8%), two intrauterine deaths (8.7%), five postnatal deaths (before or after surgery) (21.7%); the remaining eight neonates (34.8%) are alive and thriving after surgery (six) or awaiting surgery (two). Conclusions: CAT can be reliably diagnosed and characterised in prenatal life, although differentiation from PAVSD may be challenging. The association with chromosomal anomalies is consistent (8.7%), but there is a higher risk of 22q11 microdeletion (31.6%), in agreement with postnatal studies. The relatively poor survival rate (34.8%) reflects the high rate of terminations and the unfavourable cardiac anatomy in some cases.